RMS News (Res Medica, 2014)
Senior President: Donald Macarthur1st Junior President: Mary Dolan2nd Junior President: Louise Smith3rd Junior President: Sigrid WanlessSecretary: Stuart BlakeJunior Secretary: Clare MilesTreasurer: Dr. Brian MontgomeryBusiness Convener: Aileen McKinley, Paul MacKenneyPublicity Convener: Caroline CobbHouse Convener: Kneale MetcalfLibrary Convener: Emily CobbMuseum Convener: Simon HartEntertainments Convener: Agneta Fullarton